High-rate in-plane micro-supercapacitors scribed onto photo paper using in situ femtolaser-reduced graphene oxide/Au nanoparticle microelectrodes. Issue 4 (24th February 2016) - Li, R.-Z.; Peng, Rui; Kihm, K. D.; Bai, S.; Bridges, D.; Tumuluri, U.; Wu, Z.; Zhang, T.; Compagnini, G.; Feng, Z.; Hu, A.
Abstract : Direct laser-reduction of graphene oxide (GO), as a lithography-free approach, has been proven effective in manufacturing in-plane micro-supercapacitors (MSCs) with fast ion diffusion. Abstract : Direct laser-reduction of graphene oxide (GO), as a lithography-free approach, has been proven effective in manufacturing in-plane micro-supercapacitors (MSCs) with fast ion diffusion. However, the power density and the charge/discharge rate are still limited by the relatively low conductivity of electrodes. Here, we report a facile approach by exploiting femtolaser in situ reduction of the hydrated GO and chloroauric acid (HAuCl4 ) nanocomposite simultaneously, which incorporates both the patterning of rGO electrodes and the fabrication of Au current collectors in a single step. These flexible MSCs boast achievements of one-hundred fold increase in electrode conductivities of up to 1.1 × 10 6 S m −1, which provide superior rate capability (50% for the charging rate increase from 0.1 V s −1 to 100 V s −1 ), sufficiently high frequency responses (362 Hz, 2.76 ms time constant), and large specific capacitances of 0.77 mF cm −2 (17.2 F cm −3 for volumetric capacitance) at 1 V s −1, and 0.46 mF cm −2 (10.2 F cm −3 ) at 100 V s −1 . The use of photo paper substrates enables the flexibility of this fabrication protocol. Moreover, proof-of-concept 3D MSCs are demonstrated with enhanced areal capacitance (up to 3.84 mF cm −2 at 1 V s −1 ) while keeping high rate capabilities. This prototype of all solid-state MSCs demonstrates the broad range of potentials of thin-film based energy storage device applications for flexible, portable, and wearable electronic devices that require a fast charge/discharge rate and high power density.